Performance of Health Officers And Family Support in Motivating For The Utilization of Integrated Non-Communicable Diseases (Posbindu PTM) - Nunung Syamsuddin; Hardin Hardin; Amran Razak; Muhammad Alwy Arifin (Asia Pacific Journal of Health Management)
Integrated services for noncommunicable diseases (NCDs) are important public health services for the management and prevention of NCDs. However, lack of motivation to use these services remains a challenge. Factors such as health worker performance and family support may be associated with this problem. Therefore, this study aimed to examine the association of these factors with motivation to use integrated NCDs services (Posbindu PTM).